The EU external policy of promoting human rights and Vietnam’s legalization of human rights - Trinh, Hai Yen (Đại học Quốc Gia Hà Nội, 2020)
This paper examines the content and tools of the EU foreign policy in terms of promoting human rights in third countries as well as its impact on Vietnam’s legislative development. Under its external policies, the EU aims at fostering human rights worldwide, upholding the universality and indivisibility of human rights, though its external actions on economic, social and cultural rights are less elabourated than those on civil and political rights. It has designed the framework governing the formulation, implementation and assessment of these policies. The EU integrates the promotion of human rights in all aspects, including trade, investment, technology and telecommunications, the Internet, energy, environment, corporate social responsibility and development policy as well as in Common Security and Defence Policy (CSDP) and the external dimensions of employment and social policy and the area of freedom, security and justice, including counter-terrorism policy. It has employed multiple economic and political instruments to promote human rights abroad such as Generalised System of Preferences, the European Instrument for Democracy and Human Rights, sustainable development chapters of the EU trade agreements, political, human rights dialogues, public declarations, statements, etc. These are also applicable in the case of Vietnam. There exists some impact or correlation between changes in the Vietnam’s legal framework on safeguarding human rights and the EU recommendations on the same subject matters is without having to conduct a comprehensive review of all internal and external driving forces for those changes. The first law-making changes discussed is Vietnam’s conclusion of new treaties which are mentioned in human rights dialogues and the FTA with EU. Second, revising domestic laws and new draft law projects appear to be consistent with the rights and freedoms prioritized by the EU in its external relationship with Vietnam.